Current problems of banking investment development in Ukraine. - Третякова, Олена Василівна; Харабара, Віолетта; Грешко, Роман Ігорович (My University, 2021)
In a developed market economy, banks are leaders not only in the credit market, but also in the investment sphere, as they provide investment loans and effective investments in stock market instruments. Bank investments can have a positive effect on increasing the volume of investment resources to ensure the accelerated development of the national economy. Banking institutions increase their investment potential through the issuance and placement of their own securities, financial intermediation, as well as through the development of market infrastructure, expanding their professional activities.
Keywords: banks; banking system; credit; banks capital